Faktor Risiko Kejadian Low Back Pain Pada Operator Tambang Sebuah Perusahaan Tambang Nickel Di Sulawesi Selatan - Basuki, Kristiawan (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: Low back pain (LBP) is a common clinical syndrome of musculoskeletal disorders on the lumbar vertebra area. LBP mostly occurred on a heavy work involving physical and heavy machine or vehicle. PT.INXX is one of the biggest Indonesian nickel mining company which employ 700 mining operators. Since March 2007-2008 there were 212 cases of LBP. This study aims to determine the risks factors of Low Back Pain occurrence among mining or heavy vehicle operators.Method: Case control study involved 65 respondents as case and 65 respondents as control. Respondents were randomly selected with more than five years service as inclusion criteria. Data were analyzed univariate, bivariate (chi-square) and multivariate (logistic regression).Result: It was found type of vehicle, exercise and work stress significantly correlated to LBP occurrence whilst age, obesity and smoking habit were not significantly correlated to LBP. Logistic regression analysis showed that the type of vehicle was the strongest predictor of low back pain.Keywords: Low, back, pain, risk, heavy, vehicle, operator, mining